Existence and Uniqueness of Mild Solutions for Nonlinear Stochastic Impulsive Differential Equation - L. J. Shen; J. T. Sun (Abstract and Applied Analysis)
This paper investigates the existence and uniqueness of mild solutions to the general nonlinear stochastic impulsive differential equations. By using Schaefer's fixed theorem and stochastic analysis technique, we propose sufficient conditions on existence and uniqueness of solution for stochastic differential equations with impulses. An example is also discussed to illustrate the effectiveness of the obtained results.